Can Initial Glycemic Control Predict Metformin Failure in Women with Gestational Diabetes? [38B]. (May 2018) - Persad, Malini D.; Ou, Jennie; Bernasko, James; Garry, David; Garretto, Diana; Herrera, Kimberly
Abstract : INTRODUCTION: To determine if glycemic control prior to medication initiation predicts metformin failure in women with gestational diabetes (GDM). METHODS: A retrospective cohort study of women with GDM was conducted from 2013-2016. Included in the study were women with GDM started on metformin after a failed trial of diet therapy. Excluded from the study were women with pre-existing DM. Women were advised to take fasting and 1-hour postprandial finger sticks. Women were categorized as having adequate glycemic control on metformin (metformin success) or requiring the addition of or transition to an insulin regimen (metformin failure). Maternal demographics and average blood glucose (BG) values were collected. The sensitivity and the specificity of BG values as a screening test for metformin failure were analyzed and the corresponding ROC curves were plotted to assess the performance of the test. Parametric and nonparametric statistical analyses were performed with a p value of <0.05 as significant. RESULTS: A total of 118 gestational diabetics were identified, 19 (16.1%) women failed metformin therapy. There were no significant differences in maternal demographics in the groups. Compared to the metformin success group, those in the metformin failure group had significantly higher fasting BG values prior to medical management. Postprandial BG values were not different between groups. A ROC curve of the average fasting BGs revealed that a value of 90mg/dl was best predictive of metformin failure (AUC 0.74; p 0.002), with a sensitivity and specificity of 90% and 79% respectively. CONCLUSION: Elevated fasting BG values may predict metformin failure in women with GDM.